Analyzing Lexico-Grammar in EFL Learners’ Argumentative Essays Using the Transitivity System: Analisis Leksiko-Gramatika dalam Esai Argumentatif Pembelajar EFL dengan Menggunakan Sistem Transitivitas - Nurkholidah, Endang Siti; Muhria, Lanlan (Edukasi: Journal of Educational Research, 2025)
This study aims to examine the lexico-grammatical choices in an EFL learner’s argumentative essay using the transitivity system. It seeks to assess the quality of the learner’s writing to help improve their writing ability. The study also explores the experiential meaning constructed by the learner to persuade the reader through her argumentative text. In terms of methodology, this research employs document analysis to investigate the transitivity system. The data is from an argumentative essay written by an EFL learner at a state university in Cirebon. A qualitative approach is used, specifically textual analysis, a data analysis method that closely examines texts' content, meaning, structure, and discourse. The result shows that the material process takes over half of the portions of all process types. It indicates that the EFL Learner only serves a few arguments in the text. Thus, the argumentative essay text written by EFL learners has not fulfilled the standard quality of writing an argumentative essay. It is clearly shown from the result of finding process types, which should be mental and verbal processes as the highest portions in the text. This study contributes to the understanding of how transitivity analysis can reveal the strengths and weaknesses in EFL learners' argumentative writing, with implications for developing more targeted pedagogical strategies to enhance students' ability to construct effective arguments.